Lipid Peroxidation and Hemostatic Disorders in the Pathogenesis of Toxemia in Patients with Destructive Pneumonias - S. P. Lapshin; V. T. Dolgikh; K. K. Kozlov (Общая реаниматология, 2007)
Objective: to study a role of lipid oxidation processes and hemostatical disorders in the pathogenesis of endogenous intoxication in patients with varying destructive complications of severe pneumonia. Subjects and methods. Sixty-two patients with destructive complications of severe pneumonia were examined; the parameters of endotoxicosis, lipid peroxidation, and impairments in the blood aggregation regulatory system were studied. Results. An acute destructive process has been established to be attended by the higher rates of lipid peroxidation, which causes phasic changes in catalase activity. Enhanced platelet functional activity in the presence of endotheliopathy and plasma thrombinemia results in the increased uptake of coagulation factors; inhibited fibrinolysis promotes the progression of microthrombogenesis, which presents as disseminated intravascular clotting (DIC). Conclusion. The accumulation of lipid peroxidation products is shown to substantially aggravate the course of a pathological pulmonary process in destructive complications of community-acquired pneumonia. Elevated thrombinemia in the presence of endotheliopathy induces acute DIC. Key words: pneumonia, destructive complications, endotoxemia, lipoperoxida-tion, hemostatic disorders.